Customer Orientation and Leadership in the Health Service Sector: The Role of Workplace Social Support - Bruno, Andreina; Dell’Aversana, Giuseppina; Zunino, Anna (Frontiers in Psychology, 2017)
Health care is a critical context due to unpredictable situations, demanding clients, workload and intrinsic organizational complexity. One key to improve the quality of health services is connected to the shift in organization perspective of viewing patients as active consumers rather than passive users. Therefore higher levels of customer orientation are expected to improve organizational service effectiveness. According to a cultural perspective to customer orientation, the aim of the study is to explore how different leaders’ behaviors (task-oriented and relationship-oriented) interact with customer orientation of health organizations. Specifically, the aim of the paper is to contribute to this topic, by considering the leaders’ point of view. Since leader’s experience of customer orientation is influenced by social processes in the work environment, workplace social support was inserted as moderator in the relationship between leader behavior and customer orientation. A survey study was conducted among 57 Health Department Directors belonging to the National Health Service in the North of Italy in 2016. Findings showed that workplace social support moderated the influence of leadership concern for relationship on costumer orientation. Practical implications of the study are discussed.